Penguatan Peran Serta Organisasi Kemasyarakat dan Mitra Kerja dengan Penyuluhan Mengenai Indikasi dan Kontraindikasi Pemasangan Alat Kontrasepsi - Asmarani, Sri Utami; Heryani, Heni (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: The success of the population and family planning programme is marked by among others a decrease in the population growth rate, a decrease in the fertility rate, an increase in public awareness of the meaning of a small family, an increase in community awareness and participation in managing the family planning programme carried out by the Rural Community Institutions (IMP) cadres. Objective: The purpose of this community service is expected to increase the knowledge IMP cadres with counselling on indications and contraindications for contraceptive insertion so as to increase the success of the family planning programme in the community. Method: The method of implementation is by providing counselling on indications and contraindications for contraceptive insertion. Result: There were 52 IMP cadres who attended counselling on indications and contraindications for contraceptive insertion. The pre-test results before counselling showed that 68% of IMP cadres were able to answer questions correctly. After counselling, posttest results showed that almost all (93%) IMP cadres could answer questions correctly. This proves that the counselling provided can increase the knowledge and understanding of IMP cadres regarding indications and contraindications for contraceptive insertion. Conclusion: The targets were very enthusiastic in participating in this activity. This was evidenced by the number of participants who asked questions when the presentation of the material was finished. The role of IMP cadres is very important in reminding couples of the importance of participating in the family planning programme, and choosing the right contraceptive.